Hepatotoxic reactions during treatment of newly diagnosed patients with pulmonary multiple drug resistant tuberculosis - R. Yu. Аbdullаev; O. G. Komissаrovа; E. S. Chumаkovа; V. S. Odinets; A. E. Ergeshov (Туберкулез и болезни лёгких, 2019)
216 new pulmonary tuberculosis patients suffering from multiple drug resistance (MDR) were examined. The patients were divided into 2 groups. The first group consisted of 164 patients in whom when admitted to hospital, GeneXpert MTB/RIF was used to test the resistance of Mycobacterium tuberculosis (MTB) to rifampicin. Initially, patients in this group were treated with chemotherapy regimen 4 (pyrazinamide, kanamycin/amikacin/capreomycin, fluoroquinolones, cycloserine/terizidone, prothionamide, PAS). Group 2 included 97 patients. They all were treated with chemotherapy regimen 1 (isoniazid, rifampicin, pyrazinamide, ethambutol/streptomycin) before MDR was confirmed in them by sputum culture on solid media (in 2-3 months of treatment) after that treatment regimen was amended with re-registration for chemotherapy regimen 4. It was found out that hepatotoxic reactions in patients without initial abnormal liver function when prescribing chemotherapy regimen 4 occurred in 31.3% of cases and when initially using regimen 1 followed by switching to regimen 4 – in 87.8% of cases ( p < 0.001). In the course of treatment, the signs of liver damage in patients who initially received regimen 4 were more frequent in the first 2 months of treatment, whereas in patients treated initially with regimen 1 with subsequent switching to regimen 4 – during the first 4 months. In the overwhelming majority of cases, hepatotoxic reactions were mild in patients who initially received regimen 4 as well as in patients initially treated with regimen 1 followed by switching to regimen 4. However, severe hepatotoxic reactions were more often observed in patients from Group 2.